2014
DOI: 10.7717/peerj.341
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of evaluating pain and a pre-incisional local anesthetic block

Abstract: Background. Our objective was to test the effectiveness of a local anesthetic line block administered before surgery in reducing postoperative pain scores in dogs undergoing ovariohysterectomy (OVHX).Methods. This study is a prospective, randomized, blinded, clinical trial involving 59 healthy female dogs. An algometric pressure-measuring device was used to determine nociceptive threshold, and compared to three subjective pain scales. Group L/B received a line block of lidocaine (4 mg/kg) and bupivacaine (1 mg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
(36 reference statements)
2
13
0
4
Order By: Relevance
“…The individual factors regarding the way of feeling pain for patients and the preferences might also be of great importance [14][15][16]. Our findings have shown that women are statistically less frequent to report pain.…”
Section: Discussionsupporting
confidence: 55%
“…The individual factors regarding the way of feeling pain for patients and the preferences might also be of great importance [14][15][16]. Our findings have shown that women are statistically less frequent to report pain.…”
Section: Discussionsupporting
confidence: 55%
“…Hence there was no evidence to support technical failure in the animals that required early rescue analgesia. An alternative explanation is that the CMPS-SF might not be able to discriminate anxiety or dysphoria from pain behavior (McKune et al 2014). That being the case, animals experiencing emergence dysphoria could have received pain scores that erroneously indicated a need for rescue analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…; McKune et al. ). The pre‐ and post‐INC administration of bupivacaine ± lidocaine did not show analgesic benefits in two studies (Fitzpatrick et al.…”
Section: Introductionmentioning
confidence: 98%
“…; McKune et al. ). The combination of IP and INC bupivacaine was shown to provide effective analgesia in one study (Carpenter et al.…”
Section: Introductionmentioning
confidence: 98%